Perlindungan Hukum Saksi dan Korban Oleh Lembaga Perlindungan Saksi dan Korban - Adhytia, Putra; Leo, Rudepel Petrus; Amalo, Heryanto (Law Faculty, Nusa Cendana University, 2024)
Witnesses are one of the valid evidence in the trial process, sanctions are people who are present or 2 the incident themselves while it is taking place, the presence of witnesses and victims is very meaningful because law enforcement officials face difficulties when searching and obtaining evidence carried out by the suspect which causes violence to the victim. The success or failure of the judicial process depends so much on the level of witnesses and victims who are successfully met and exposed in the sequence of events in the contest, which are mainly directly related to the explanation of witnesses, often cases that cannot be revealed because there is no testimony from witnesses that can support the duties of law enforcement. Protection of witnesses and victims is currently urgent to be held in every checking session in cases that are considered to require special attention and very tight guard. from this problem, the author discusses the problems, namely: (1) how is the implementation of the mechanism for providing legal protection to witnesses and victims by the LPSK (2) what are the factors that affect the effectiveness of providing legal protection to witnesses and victims by the LPSK. This research uses empirical research methods, while the data sources used are primary and secondary. The results of this study are: (1) to obtain protection must first apply for protection to the LPSK by fulfilling the conditions determined after receipt of the protection application, the protected will get legal protection and fulfillment of rights. (2) Factors that affect the effectiveness of protection are legal facts, law enforcement, facilities and facilities, community factors, and cultural factors. Suggestion: This institution should become an independent institution to provide comprehensive protection and the importance of the presence of this institution in the region so that legal protection feels optimal, not centralized in the center and the need for an introduction to this institution so that the public who lays about the law can know the existence of this institution.